Methodical Principles of Calculation and Analysis of Opened Power Network with Several Power Supply Sources - M. I. Foursanov; A. A. Zolotoy; V. V. Makarevich; A. N. Moukha (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2009)
The paper presents methodical principles for analysis of opened 10(6) kV power network modes with symmetrical and asymmetrical phase loads. A mathematical model and an algorithm of sectional point optimization in the distributive 10(6) kV power network has been modified in the paper. The problem is solved with due account of  power supply network of 110 kV and higher and a number of additional limitations. The obtained algorithms serve as a basis for development of the required complex of industrial programs for solution of technological problems pertaining to operation of urban 10(6) kV power networks.